P120-连环蛋白介导钙黏蛋白转换促进口腔鳞状细胞癌细胞迁移和侵袭的实验研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2017)
OBJECTIVE: The main goal is to investigate the role of P120-catenin (P120(ctn)) in cadherin switching, as well as migration and invasion, of oral squamous cell cancer (OSCC) cells. METHODS: The plasmid pGFP-V-RS-P120(ctn) shRNA was used to transfect TSCCA cells and significantly reduce the expression of P120(ctn) in these cells. Real-time fluorescent quantitative polymerase chain reaction and Western blot were conducted to determine the mRNA and protein expression levels of P120(ctn), E-cadherin (E-cad), and N-cadherin (N-cad). By contrast, the Transwell cell invasion and cell migration assay was used to determine the invasion and migration capacities before and after the transfection. RESULTS: After the plasmid pGFP-V-RS-P120(ctn) shRNA was transfected into the TSCCA cells, we found that as the P120(ctn) expression significantly decreased, E-cad mRNA and protein expression decreased significantly. Moreover, N-cad mRNA and protein expression increased significantly (P<0.05). Lastly, the cell migration and invasion capacities were augmented significantly (P<0.05). CONCLUSION: In OSCC cells, P120(ctn) may be involved in cadherin switching and promote metastasis and invasion.